Isolation of Neisseria meningitidis from the Genito-Urinary Tract and Anal Canal - Faur, Yvonne C. (1975)
During the first 3 months of 1975, a striking increase has been noted in the incidence of Neisseria meningitidis in cultures from the genito-urinary tract and anal canal of both males and females being screened for gonorrhea. The data for recovery of these organisms from these sites are presented and reviewed.